Gold catalysis in total synthesis – recent achievements. (17th December 2015) - Pflästerer, Daniel; Hashmi, A. Stephen K.
Abstract : The most recent achievements of gold catalysed transformations applied in total synthesis of natural products are reviewed and analysed. Abstract : In this critical review the applications of gold catalysed reactions in total synthesis during the years since our last article are reviewed. At the end of this article a literature analysis is conducted to evaluate the progress in this field.